Strategies and Tactics in Supply Chain Event Management - Ijioui, Raschid.; Ijioui, Raschid.; Emmerich, Heike.; Emmerich, Heike.; Ceyp, Michael.; Ceyp, Michael. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book gives unique insights into the Supply Chain Event Management (SCEM) of world-leading companies. Aims, methods, instruments as well as resources and budgets in Supply Chain Event Management are discussed. The reader will gain a strong understanding of the way to deal with problems along the supply chain and how to avoid them. Supply Chain Event Management is a transparent view of the company and all value chain partners and allows to meet timelines with decreased cost and risks.